LA VILLE D’ABENGOUROU ET SA CAMPAGNE: DES RELATIONS VILLECAMPAGNE CROISEES - Ahoua Téhia Eliane; Loba Akou Don Franck-Valéry; Dakourı Guissa Desmos Francis; Aloko-N’guessan Jérôme (European Scientific Journal, ESJ, 2015)
Historically, the big urban poles always exercised a strong influence, both economic as social political or cultural, on campaigns. However, the city of Abengourou, administrative center of region which is in a zone with economy of plantation maintains relations of interaction with its campaign. This study shows that the relations city-campaign in the department of Abengourou are characterized by mutual exchanges. The methodological approach used in this study articulates around three points namely: the document retrieval, the field works and the data analysis with the model free format which was used. The obtained results highlight city-dwellers strongly attached to their village, relations in the sense campaign.